2014
DOI: 10.1159/000365288
|View full text |Cite
|
Sign up to set email alerts
|

The Dissection Profile and Mechanism of Tissue-Selective Dissection of the Piezo Actuator-Driven Pulsed Water Jet as a Surgical Instrument: Laboratory Investigation Using Swine Liver

Abstract: Background/Purpose: The water jet technique dissects tissue while sparing cord-like structures such as blood vessels. The mechanism of such tissue-selective dissection has been unknown. The novel piezo actuator-driven pulsed water jet (ADPJ) system can achieve dissection with remarkably reduced water consumption compared to the conventional water jet; however, the system's characteristics and dissection capabilities on any organ have not been clarified. The purposes of this study were to characterize the physi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 34 publications
0
28
0
Order By: Relevance
“…Clinical case reports showed that a water jet with a pressure of 1000 to 1500 psi can selectively strip the stomach mucosa of the pig while causing minor damage to deeper tissue . In addition, another article reported that various components of the liver have various tolerance levels to water pressures, that is, for the liver parenchyma it was 87 to 341 psi, for the hepatic vein it was 876 to 1769 psi, and for the Glisson sheath it was 2364 to 8717 psi . How is it working on skin tissues?…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Clinical case reports showed that a water jet with a pressure of 1000 to 1500 psi can selectively strip the stomach mucosa of the pig while causing minor damage to deeper tissue . In addition, another article reported that various components of the liver have various tolerance levels to water pressures, that is, for the liver parenchyma it was 87 to 341 psi, for the hepatic vein it was 876 to 1769 psi, and for the Glisson sheath it was 2364 to 8717 psi . How is it working on skin tissues?…”
Section: Discussionmentioning
confidence: 99%
“…• the present investigation is for the first time to demonstrate the selectivity of hydrosurgery system in debridement of burn wound • 50 burn wounds were created, hydrosurgery system was used to debride both burn wound and normal skin, histological analysis was performed thereafter • resection rate was significantly higher in the burn wound compared with the normal skin when the applied water pressure of hydrosurgery system range from 3000 to 5000 psi undergoing hydrosurgery. 15 Moreover, Kaehler et al reported that using the hydrosurgery system, the pig's gastric mucosa was stripped without damaging the stomach smooth muscle layer. 16 However, no report shows whether the hydrosurgery has a capability of tissue selectivity in the burn wound debridement.…”
Section: Key Messagesmentioning
confidence: 99%
See 1 more Smart Citation
“…CUSA is a surgical device dissecting tissues using tissue selectivity of supersonic vibration, but morphological structure after dissecting the tissues might be different between the ADPJ system and CUSA. Yamada et al (2014) reported that hepatectomy using the ADPJ system resulted in histologically less injury than the existing radio knife, the ultrasonic surgical system and the ultrasonic cutting shears in swine. The morphological structure after dissecting the liver parenchyma by the ultrasonic surgical system was destroyed, and the blood vessels and bile ducts were not preserved.…”
Section: Discussionmentioning
confidence: 99%
“…Nitta gelatin 1st Grade (G1211; Nitta Gelatin, Inc.), 3.5 wt% (gelatin weight/total weight) was dissolved in warm water and cooled to solidify at 280 K. Gelatin blocks with this composition have equivalent mechanical profiles to the brain parenchyma, so they can be used as a model of brain tissue. 17,21 The gelatin specimen was immersed into physiological saline, and the nozzle of the ADPJ was placed perpendicularly to the gelatin surface. A pulsed or continuous-flow water jet was ejected at different flow rates, and the cutting depth was measured.…”
Section: Evaluation Of Dissection Profile In Brain Phantom Experimentsmentioning
confidence: 99%